Market Concentration in Industrial and Commercial Non-Hazardous Waste Valorisation: The Case of Chile - Vasquez-Perez, O; Espinoza-Perez, A (Elsevier Ltd, 2024)
Market concentration among buyers of recycled materials is a phenomenon discussed since the 1980 s by the anti-trust literature. Yet, there is still a lack of studies on simultaneous market concentration on both the supply and demand sides. This is particularly relevant when Extended Producer Responsibility (EPR) policies produce two-sided waste generation and valorisation markets. Thus, the purpose of this study is to explore the link between market concentration on the generation side and market share on the valorisation side. Specifically, this research addresses the case of valorisation of commercial and industrial non-hazardous waste in Chile. The analysis covers 261 companies that valorised industrial and commercial non-hazardous waste between 2015 and 2019. Being part of the top 10 % of generator companies in Chile is significantly correlated to higher valorisation market share, in a context in which mean market share per company decreased, total tons valorised stagnated, and the country-level valorisation rate diminished. © 2024 Elsevier Ltd